Cathodic shift of a photo-potential on a Ta3N5 photoanode by post-heating a TiO2 passivation layer. Issue 49 (14th June 2017) - Liu, Jie; Luo, Wenjun; Zhu, Kaijian; Wen, Xin; Xiu, Fei; Yuan, Jiajie; Zou, Zhigang; Huang, Wei
Abstract : A 90 mV cathodic shift of photo-potential of a Ta3 N5 photoanode is achieved by increasing the conductivity of a TiO2 passivation layer. Abstract : Ta3 N5 is a promising photoanode material for solar water splitting due to its suitable band gap and high theoretical solar energy conversion. A high onset potential of Ta3 N5 limits its photoelectrochemical performance due to serious surface charge recombination. In a previous study, a TiO2 passivation layer was usually coated on the surface of Ta3 N5 to reduce the surface recombination and improve the performance of a sample. However, to date, there are no studies on the effect of conductivity of the TiO2 passivation layer on the photoelectrochemical properties of a Ta3 N5 photoanode. In this work, for the first time, the conductivity of TiO2 is increased by post-heating of a TiO2 passivation layer, leading to a 90 mV cathodic shift of the photo-potential of Ta3 N5 . After further loading with a Ni(OH) x /FeOOH bi-layer electrocatalyst, the Ta3 N5 photoanode achieves a current density of 6.4 mA cm −2 at 1.23 VRHE and a HC-STH (half-cell solar to hydrogen efficiency) of 0.72% under a sunlight simulator (100 mW cm −2 ), which are the highest values among the Ta3 N5 photoanodes prepared by thermal oxidation and nitridation of Ta foil.